System zarządzania przedsiębiorstwa oraz metody jego doskonalenia: Uwagi metodyczne - Malara, Zbigniew (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The paper concerns important aspects of management system of contemporary enterprise and its development. Rudimental conceptions, models and approaches and tools, useful in accomplishing changes within the management system are described. Finally any conclusions are given as well. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1184, s. 48-56